Risk factors associated to fetal death - Aquino, Márcia Maria Auxiliadora de; Cecatti, José Guilherme; Mariani Neto, Coríntio (São Paulo Medical Journal, 1998)
OBJECTIVE: The purpose of this study was to investigate risk factors associated to fetal death in a Brazilian population. DESIGN: A case control study. SETTING: The Hospital Maternidade Leonor Mendes de Barros in São Paulo. PARTICIPANTS:122 pregnant women with diagnosis of fetal death and gestation age of 20 or more weeks and 244 controls of pregnant women who delivered liveborns. VARIABLES STUDIED: The fetal death (dependent variable), independent variable (the social demographic factors, clinical and obstetrical history, prenatal care indicators and pathological conditions). RESULTS: The risk factors associated to fetal death were abruptio placentae, syphilis, few prenatal care visits, one or more previous stillbirths, hospitalization during pregnancy, diabetes, age above or equal to 25 years, hypertension during pregnancy, anemia and age below 20 years. CONCLUSIONS: Results of the current study might be useful to orientate a primary prevention health program, specially those concerning antenatal care.